Field enhanced in-plane homostructure in a pure MoSe2 phototransistor for the efficient separation of photo-excited carriers. Issue 5 (30th November 2018) - Deng, Wenjie; Wang, Yi; You, Congya; Chen, Yongfeng; Zhang, Yongzhe
Abstract : A homojunction as a photoresponse enhancement scheme in a pure MoSe2 device is introduced. Abstract : Two-dimensional transition-metal dichalcogenides (TMDs) have attracted significant attention, owing to their excellent electrical and optoelectrical properties, especially MoS2 . However, the photoresponse of pure MoSe2 is still unsatisfactory due to the absence of a photoresponse enhancement mechanism, which impedes its rapid development in optoelectronics. Here, we report a pure MoSe2 phototransistor with an in-plane lateral thickness-dependent MoSe2 homojunction in the channel perpendicular to the charge transfer direction as an enhancement scheme for the first time. An in-plane lateral built-in field is spontaneously formed due to the different electrical band structure of MoSe2 with different thickness, which facilitates the efficient separation of photo-excited carriers. Furthermore, with an increase in the applied negative back-gate voltage, separation could be further strengthened due to the increase of the built-in field in the homojunction resulting in optimization of the photoresponse performance. These results suggest a facile approach for the enhancement of photoresponse performance to materials which possesses a thickness-dependent energy band structure.